THE EFFECT OF EQUITY ON PROFITABILITY AND RISK: A COMPARATIVE STUDY BETWEEN ISLAMIC AND CONVENTIONAL BANKS - Hamida, Arafet; Lanouar, Amira (International Journal of Islamic Business & Management, 2024)
The nature of the relationship between equity and risk as well as equity and profitability has been the subject of two basic hypotheses in the literature: the structure-behavior-performance (SCP) approach for the capital-profitability relationship and the moral hazard approach for the capital-risk relationship. The objective of this article is to study the relationship between equity and risk and equity and profitability for 215 banks from 18 emerging countries. This study focuses on Islamic banks and conventional banks. We use a GMM estimator. The results obtained for Islamic banks regarding the relationship between equity and risk did not confirm the moral hazard hypothesis. Indeed, equity has a positive effect on risk with the three measures used (the variance of average economic profitability, the variance of average financial profitability, and the logarithm of Z-Score). The same goes for conventional banks. An increase (decrease) in capital leads to an increase in risk (decrease). As for the relationship between equity and profitability, we found a difference in results for the two types of banks studied (Islamic and conventional). Indeed, for Islamic banks, the SCP (structure-behavior-performance) theory is not verified. An increase (or decrease) in capital leads to a decrease (or increase) in profitability. This was found for the three profitability specifications used (average economic profitability, average financial profitability, and net interest margin). For conventional banks, equity positively affects profitability with its different measures, which is consistent with the structure-behavior-performance paradigm. JEL Classification Codes: G21, C23.